La importancia de la valoración psicológica en la violencia sexual digital - Suárez Andrade, Gabriel Eduardo (2025)
Digital sexual violence is an emerging and complex issue that primarily affects women, girls, and adolescents, causing profound psychological and legal implications. This type of violence, facilitated and exacerbated by the use of digital technologies, not only infringes upon victims' rights but also poses significant challenges in terms of its identification, prosecution, and reparation for the harm caused, particularly the psychological damage experienced by the victims. In this context, psychological assessment becomes an essential tool in judicial processes, enabling the scientific evaluation of the psychological impact on victims and its causal relationship with the acts of violence suffered. This research aims to analyze the importance of psychological assessment in cases of digital sexual violence, understood as a key mechanism for determining responsibilities and psychological harm in judicial proceedings. The methodology employed was both qualitative and quantitative, utilizing historical-logical, analytical, and documentary methods, complemented by interviews and surveys designed to obtain favorable results regarding the research topic and objectives. The findings reveal the growing prevalence of digital sexual violence, its significant psychological impact on victims, and the need to strengthen the role of psychological expertise in determining accountability. Furthermore, the importance of an interdisciplinary approach between the legal and psychological fields is highlighted to address this issue effectively.